Learning to Read and Reading to Learn in English - Pokharel, Parbati Kumari (Journal of NELTA Surkhet, 2018)
Reading is one of key language skills which enables the readers to learn many things i.e. reading is the gateway of knowledge. Enabling the readers to read in English is one of the major issue in ELT. This article defines reading as the key skill with various reading strategies and comprehension as the goal of reading. It is based on the secondary sources of data basically based on the review of related literature and attempts to review on learning to read and reading to learn in English in particular.Journal of NELTA Surkhet,  Vol. 5 January, 2018, Page: 75-81